Influence of Rainfall and Rainy Day on Oil Palm Production 8, 16, and 19 Years Aged In Bah Jambi Plantation PT. Perkebunan Nusantara IV Persero - Yolan Surya Barus (Universitas Sumatera Utara, 2016)
This research was to determine the effect of rainfall and rain day as well as the correlation of both on oil palm production in plants aged 8, 16 and 19 years. This research was held at PTPN IV Unit Bah Jambi from May 2015 until August 2015. This research used primary data such as the production of fresh fruit bunches (FFB); componen production data as total bunches, average bunches weight, and total of productive trees; rainfall data and rain day monthly in 2011, 2012, and 2013. Analysis method used are double linier regression and correlation analysis by using statistic software SPSS.v.17 for windows. The regression analysis shows that rain fall and rain day variables significanted with alpha 5% (Sig < α 0.05) to increase the production of FFB at the age of 16 years and unsignificanted to increase the production of FFB at the age 8 and 19 years. Correlation results in plants was 8, 16, and 19 years with two-way analysis test at 1% level showed variable rainfall and rainy days have a strong relationship, and the real (positive) direction. Correlation values ​​of rainfall and rainy days are 0.848; 0.901; and 0.851 each with significant level < α 0,01.